Abdominal hysterectomy: analysis of clinico-histopathological correlation in Western Rajasthan, India - Yadav, Dinesh Pal; Yadav, Ramgopal; Bhati, Indra (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Hysterectomy is the most common gynecological surgery done in the females worldwide as it provides definitive cure to a wide range of gynecological diseases, both benign and malignant. The indications to perform this major surgery should always be justified and the pathology should be proved histopathologically. Histopathological analysis and review is mandatory to evaluate the appropriateness of the hysterectomy. Methods: A retrospective, longitudinal study was conducted in the Department of Obstetrics and Gynecology, UMAID Hospital, Dr. S.N. M.C. Jodhpur (Raj.) during October 2014 to March 2015.Total 105 cases were studied during this period. The study included all women undergoing planned abdominal hysterectomy. Data was recorded on proformas, including demographic characteristics and clinical features. Hysterectomy specimens were saved in 10% formalin and sent to the Department of Pathology. Histopathology reports were analyzed and compared with the indications of surgery to draw various informative conclusions. Results: Of 105 cases, 55(52.38%) were in the age group of 41 – 50, which comprised the commonest age group undergoing the surgery. Maximum women (95%) those underwent hysterectomy were multiparous. Most common preoperatively clinical diagnosis was leiomyoma uterus which was diagnosed clinically and sonographically in 51(48.57%) cases. On Histopathological examination, the commonest pathology, similar to clinical impression, was found to be Leiomyoma at 50.48% (n = 53). Adenomyosis (21.90%) was detected as Second most common pathology. Histopathological confirmation of pre-operative diagnosis was 89% for malignancy, 96% for fibroids, 100% for adenomyosis, 100% for pelvic inflammatory disease. Conclusions: There was a high correlation when the clinical diagnosis was a fibroid, adenomyosis and ovarian mass. Every hysterectomy specimen should be subjected to histopathological examination because it is mandatory for conforming diagnosis and ensuring optimal management, in particular of malignant disease.